Dominant plant species play an important role in regulating bacterial antagonism in terrestrial Antarctica - Naz, Beenish; Liu, Ziyang; Malard, Lucie A.; Ali, Izhar; Song, Hongxian; Wang, Yajun; Li, Xin; Usman, Muhammad; Ali, Ikram; Liu, Kun; An, Lizhe; Xiao, Sa; et al. (Frontiers in Microbiology, 2023)
In Antarctic terrestrial ecosystems, dominant plant species (grasses and mosses) and soil physicochemical properties have a significant influence on soil microbial communities. However, the effects of dominant plants on bacterial antagonistic interactions in Antarctica remain unclear. We hypothesized that dominant plant species can affect bacterial antagonistic interactions directly and indirectly by inducing alterations in soil physicochemical properties and bacterial abundance. We collected soil samples from two typical dominant plant species; the Antarctic grass Deschampsia antarctica and the Antarctic moss Sanionia uncinate, as well as bulk soil sample, devoid of vegetation. We evaluated bacterial antagonistic interactions, focusing on species from the genera Actinomyces, Bacillus, and Pseudomonas. We also measured soil physicochemical properties and evaluated bacterial abundance and diversity using high-throughput sequencing. Our results suggested that Antarctic dominant plants significantly influenced bacterial antagonistic composition compared to bulk soils. Using structural equation modelling (SEM), we compared and analyzed the direct effect of grasses and mosses on bacterial antagonistic interactions and the indirect effects through changes in edaphic properties and bacterial abundance. SEMs showed that (1) grasses and mosses had a significant direct influence on bacterial antagonistic interactions; (2) grasses had a strong influence on soil water content, pH, and abundances of Actinomyces and Pseudomonas and (3) mosses influenced bacterial antagonistic interactions by impacting abundances of Actinomyces, Bacillus, and Pseudomonas. This study highlights the role of dominant plants in modulating bacterial antagonistic potential in Antarctic terrestrial ecosystems.